Superplasticity and superplastic forming ability of Al-Mg-Sc alloy - 陈明和 张杰刚 李金华 芮玉龙 (Transactions of Nonferrous Metals Society of China, 2006)
The superplasticity and formability, of a cold-rolled Al-6Mg-0.2Sc alloy with coarse grains were investigated. High temperature tensile tests were performed in the temperature range of 400- 500℃ with strain rates ranging from 2.0×10^-4 to 2.0×10^-2s^-1 and the maximum clongation of 421% was obtained at 450℃ and strain rate of 2.0×10^-4s^-1. Superplastic bulging tests of a square conical shaped part were carried out under art optimum superplastic condition, with the wall thickness reduction less than 8%. which illustrates that ihe alloy has good superplastic formability,The cavities in the sections of the tensile specimens and the bulging parts were analyzed, which can bc reduced greatly by imposing proper backpressure in the bulging process.